A time-series minimally invasive transverse aortic constriction mouse model for pressure overload-induced cardiac remodeling and heart failure - Wang, Xia; Zhu, Xinxin; Shi, Li; Wang, Jingjing; Xu, Qing; Yu, Baoqi; Qu, Aijuan (Frontiers in Cardiovascular Medicine, 2023)
Transverse aortic constriction (TAC) is a widely-used animal model for pressure overload-induced cardiac hypertrophy and heart failure (HF). The severity of TAC-induced adverse cardiac remodeling is correlated to the degree and duration of aorta constriction. Most studies of TAC are performed with a 27-gauge needle, which is easy to cause a tremendous left ventricular overload and leads to a rapid HF, but it is accompanied by higher mortality attributed to tighter aortic arch constriction. However, a few studies are focusing on the phenotypes of TAC applied with a 25-gauge needle, which produces a mild overload to induce cardiac remodeling and has low post-operation mortality. Furthermore, the specific timeline of HF induced by TAC applied with a 25-gauge needle in C57BL/6 J mice remains unclear. In this study, C57BL/6 J mice were randomly subjected to TAC with a 25-gauge needle or sham surgery. Echocardiography, gross morphology, and histopathology were applied to evaluate time-series phenotypes in the heart after 2, 4, 6, 8, and 12 weeks. The survival rate of mice after TAC was more than 98%. All mice subjected to TAC maintained compensated cardiac remodeling during the first two weeks and began to exhibit heart failure characteristics after 4 weeks upon TAC. At 8 weeks post-TAC, the mice showed severe cardiac dysfunction, hypertrophy, and cardiac fibrosis compared to sham mice. Moreover, the mice raised a severe dilated HF at 12 weeks. This study provides an optimized method of the mild overload TAC-induced cardiac remodeling from the compensatory period to decompensatory HF in C57BL/6 J mice.